2019
DOI: 10.1055/a-0874-2106
|View full text |Cite
|
Sign up to set email alerts
|

CLIPPERS-Syndrom: Eine Erkrankung mit vielen Gesichtern – ein Fallbericht

Abstract: ZusammenfassungDas CLIPPERS-Syndrom ist ein chronisch entzündliches Krankheitsbild des ZNS unklarer Ätiologie, das erstmals 2010 durch die Arbeitsgruppe um Pittock beschrieben wurde. Es ist gekennzeichnet durch typische kernspintomographische Veränderungen, vorwiegend im Hirnstamm, mit entzündlichen perivaskulären, lymphohistiozytären Infiltraten und gutem Ansprechen auf eine Glukokortikoidtherapie. Hier möchten wir den Fall eines damals 40-jährigen Patienten vorstellen, der sich initial mit den typischen klin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…3,5 To find previous lymphoma-associated cases up to November 2023, PubMed and Scopus online databases were searched using the keywords "CLIPPER" and "Lymphoma". To the best of our knowledge, 20 patients with lymphoma-associated CLIPPERS have been reported [6][7][8][9][10][11][12][13][14][15][16] since the first introduction of CLIPPERS. 2 A review of 10 patients by Zhang et al showed that patients with lymphoma-associated CLIPPERS had worse clinical outcomes and higher risk of mortality compared to those without lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5 To find previous lymphoma-associated cases up to November 2023, PubMed and Scopus online databases were searched using the keywords "CLIPPER" and "Lymphoma". To the best of our knowledge, 20 patients with lymphoma-associated CLIPPERS have been reported [6][7][8][9][10][11][12][13][14][15][16] since the first introduction of CLIPPERS. 2 A review of 10 patients by Zhang et al showed that patients with lymphoma-associated CLIPPERS had worse clinical outcomes and higher risk of mortality compared to those without lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 5 To find previous lymphoma‐associated cases up to November 2023, PubMed and Scopus online databases were searched using the keywords “CLIPPER” and “Lymphoma”. To the best of our knowledge, 20 patients with lymphoma‐associated CLIPPERS have been reported 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 since the first introduction of CLIPPERS. 2 A review of 10 patients by Zhang et al.…”
Section: Discussionmentioning
confidence: 99%